Eclipta prostrata promotes the induction of anagen, sustains the anagen phase through regulation of FGF-7 and FGF-5 - Keun-Hyeun Lee; Dabin Choi; Seung-Il Jeong; Sang-Jun Kim; Chang Hyun Lee; Hyung-Sik Seo; Han-Sol Jeong (Taylor & Francis Group, 2019)
Context: Eclipta prostrata L. (Asteraceae) (EP) has been widely used for the treatment of skin disease in Asian traditional medicine. Objective: This study investigates the potency of EP in promoting hair growth in vivo and in vitro. Materials and methods: C57BL/6N mice were divided into four groups (n = 4) as follows: control (topical treatment of normal saline), topical 3% minoxidil to the dorsal skin of mice for 14 days, and low (1 mg/day) and high (10 mg/day) doses of EP orally administered once a day for 14 days. Dorsal hairs of C57BL/6N mice were depilated to synchronize anagen induction. Hair growth activity was evaluated by gross and microscopic observations. Sections of dorsal skin were stained with haematoxylin and eosin. We also treated the various concentrations of EP (5, 10 and 50 μg/mL) for 24 h on the human dermal papilla cells (HDPs) and examined the effects of EP on the expression of FGF-7 and mTOR signalling. Results: EP enhanced the induction of anagen in the dorsal skin of mice, characterized by the appearance of inner root sheath along with hair shaft, the emergence of hair shaft through the epidermis. EP increased the expression of FGF-7, while decreased the level of FGF-5 in C57/BL6 mice. EP also increased the expression of FGF-7, activated the mTOR signalling in HDPs. Discussion and conclusions: These results suggest that EP has a potency to enhance the growth of hair follicle, promoting hair growth through regulation of FGF-7 and FGF-5.